Albuminuria as a Predictor of Cardiovascular Outcomes in Patients With Acute Myocardial Infarction. Issue 8 (16th April 2019) - Mok, Yejin; Ballew, Shoshana H.; Sang, Yingying; Grams, Morgan E.; Coresh, Josef; Evans, Marie; Barany, Peter; Ärnlöv, Johan; Carrero, Juan‐Jesus; Matsushita, Kunihiro
Abstract : Background: In patients with myocardial infarction (MI), reduced kidney function is recognized as an important predictor of poor prognosis, but the impact of albuminuria, a representative measure of kidney damage, has not been extensively evaluated. Methods and Results: In the SCREAM (Stockholm Creatinine Measurements) project (2006–2012), we identified 2469 patients with incident MI with dipstick proteinuria measured within a year before MI (427 patients also had urine albumin to creatinine ratio [ACR] measured concurrently) and obtained estimates for ACR with multiple imputation in participants with data solely on dipstick proteinuria. We quantified the association of ACR with the post‐MI composite and individual outcomes of all‐cause mortality, cardiovascular mortality, recurrent MI, ischemic stroke, or heart failure using Cox models and then evaluated the improvement in C statistic. During a median follow‐up of 1.0 year after MI, 1607 participants (65.1%) developed the post‐MI composite outcome. Higher ACR levels were independently associated with all outcomes except for ischemic stroke. Per 8‐fold higher ACR (eg, 40 versus 5 mg/g), the hazard ratio of composite outcome was 1.21 (95% CI, 1.08–1.35). The addition of the ACR improved the C statistic of the post‐MI composite by 0.040 (95% CI, 0.030–0.051). Largely similar results were obtained regardless of diabetic status and when ACR or dipstick was separately analyzed without imputation. Conclusions: In patients with MI, albuminuria was a potent predictor of subsequent outcomes, suggesting the importance of paying attention to the information on albuminuria, in addition to kidney function, in this high‐risk population.